A compact band‐stop frequency selective surface for dual band Wi‐Fi applications. Issue 8 (August 2017) - Ali, Haider; Riaz, Laeeq; Naeem, Umair; Farhan Shafique, Muhammad
Abstract: This article presents a compact frequency selective surface (FSS) design which is capable of rejecting both bands of Wi‐Fi. The proposed design is evolved from a patch‐slot topology and it is investigated that the patch‐slot architecture is unstable for oblique incident waves, therefore, a number of geometrical modifications have been proposed to ensure the band stability at different incident angles. The slot geometry is modified by inductive loading and extending the slot length. The modified unit element of FSS is 0.38 λ0 at higher frequency band. Fabricated prototypes have been measured for their transmission response at incident angles upto 30° and good agreement has been observed between simulated and measured results. The proposed FSS is suitable for shielding applications and for limiting the coverage area of wireless access‐point.